Endovascular treatment with stenting of celiac artery aneurysms. Issue 48 (25th November 2020) - Yuan, Fu-Kang; Xi, Hai-Lin; Qin, Rui-Hao; Tian, Zhi-Long; Li, Cui; Lu, Fei
Abstract : Abstract: This study aimed to detail the clinical outcomes of patients suffering from celiac arterial aneurysm (CAA) that underwent treatment via stent occlusion. This is a single-center, retrospective study. A total of 8 consecutive CAA patients were treated via stent occlusion from March 2014 to September 2018 at our hospital. Follow-up computed tomography was conducted after stenting at 1, 3, 6, and 12-month time points and every year thereafter. Both short- and long-term outcomes were assessed. In total, 8 stents were inserted into these 8 patients, with 2 being uncovered and 6 being covered stents. In 2 patients, stents were positioned in the celiac artery, while in the remaining 6 patients they were placed in the celiac and common hepatic arteries. The median operative duration was 66 minutes. No patients exhibited procedure-associated complications, and the median follow-up duration was 39 months (range: 18–72). Abdominal contrast-enhanced CT analyses of these patients exhibited stent and distal artery patency in 100% of patients, together with CAA obliteration. Visceral necrosis did not occur in any patients over the follow-up period. Stent occlusion can be safely and effectively used to treat CAA patients.